Chitosan-coated nanostructured lipid carriers for transdermal delivery of tetrahydrocurcumin for breast cancer therapy. (15th July 2022) - Truong, Thien Hoang; Alcantara, Khent Primo; Bulatao, Bryan Paul I.; Sorasitthiyanukarn, Feuangthit Niyamissara; Muangnoi, Chawanphat; Nalinratana, Nonthaneth; Vajragupta, Opa; Rojsitthisak, Pornchai; Rojsitthisak, Pranee
Abstract: Chitosan (Ch)-coated nanostructured lipid carriers (NLCs) have great potential for transdermal delivery with high localization of chemotherapeutics in breast cancer. This study used tetrahydrocurcumin (THC), a primary metabolite of curcumin with enhanced antioxidant and anticancer properties, as a model compound to prepare NLCs. Response surface methodology was employed to optimize THC-loaded Ch-coated NLCs (THC-Ch-NLCs) fabricated by high-shear homogenization. The optimized THC-Ch-NLCs had particle size of 244 ± 18 nm, zeta potential of −17.5 ± 0.5 mV, entrapment efficiency of 76.6 ± 0.2% and drug loading of 0.28 ± 0.01%. In vitro release study of THC-Ch-NLCs showed sustained release following the Korsmeyer-Peppas model with Fickian and non-Fickian diffusion at pH 7.4 and 5.5, respectively. THC-Ch-NLCs demonstrated significantly enhanced in vitro skin permeation, cell uptake, and remarkable cytotoxicity toward MD-MBA-231 breast cancer cells compared to the unencapsulated THC, suggesting Ch-NLCs as potential transdermal nanocarriers of THC for triple-negative breast cancer treatment. Graphical abstract: Unlabelled Image Highlights: The optimization of THC-Ch-NLCs was achieved by response surface methodology. THC-Ch-NLCs showed sustained THC release following a diffusion-controlled release profile. Ch coating on the NLC enhanced the THC delivery through the skin. THC-Ch-NLCs remarkably enhanced the cytotoxicity of THC against both MDAMB-231 and MCF-7 breast cancer cell lines.